Recreational and small-scale fisheries may pose a threat to vulnerable species in coastal and offshore waters of the western Mediterranean. (6th May 2019) - Lloret, J; Biton-Porsmoguer, S; Carreño, A; Di Franco, A; Sahyoun, R; Melià, P; Claudet, J; Sève, C; Ligas, A; Belharet, M; Calò, A; Carbonara, P; et al.
Abstract: This study evaluates the fishing pressure exerted by the most common recreational and professional, small-scale fishing practices on vulnerable target and bycatch species in coastal and offshore waters of the western Mediterranean. By combining multiple data sources, we assembled a unique dataset on catches at multiple sites in these areas by recreational (RF) and small-scale fisheries (SSF), covering the period from 1997 to 2015. Furthermore, a framework with which to identify the vulnerable species among all the species caught is provided; it is based on the IUCN Red List, international conventions for the protection of flora and fauna, the Habitats Directive and the intrinsic vulnerability index of marine fish. Overall, about a quarter of exploited species targeted by SSF and RF in coastal waters were vulnerable, making up nearly 50% of the total SSF catch and nearly 20% of the total recreational catch. In offshore waters, 100% of the RF and SSF catch was made up of vulnerable species. Among the species caught as bycatch in both areas by SSF and RF, there was a total of 27 vulnerable vertebrate species, which included birds, cetaceans, elasmobranchs and sea turtles. Our results highlight the need to differentiate between different fishing methods or gears when studying the fishing impacts on vulnerable species. The results also indicate that, although RF and SSF are often considered to have a relatively low ecological impact, a range of different fishing methods are affecting vulnerable species in coastal or offshore waters in the western Mediterranean Sea, be they targeted or taken unintentionally as bycatch.